The therapeutic potential of thalassotherapy for enhancing well-being and reducing pharmaceutical costs in individuals with disabilities - Resta, Emanuela; Lozupone, Madia; Peter, Preethymol; Brunone, Lucia; Tafuri, Silvio; Lenato, Gennaro Mariano; Bonvino, Aurora; Taurisano, Paolo (Frontiers in Psychology, 2025)
IntroductionThalassotherapy has shown promising effects on mental and physical well-being. However, its application among individuals with intellectual disabilities, psychiatric disorders, and cognitive impairments remains underexplored. This study evaluates the therapeutic potential of thalassotherapy in reducing pharmaceutical costs and improving well-being among individuals with intellectual disabilities, psychiatric disorders, and cognitive impairments.Materials and methodsThis is an interventional cohort study that involved 144 participants aged 18 to 64 from two residential facilities in Apulia, Italy in 8 weeks. The intervention utilized seawater-based therapies at a certified thalassotherapy center, incorporating muscle awakening, music therapy, and group workshops. Participants underwent psychometric assessments using the VADO, Hamilton Anxiety Rating Scale (HAM-A), and Beck Depression Inventory (BDI) before and after the treatment.ResultsThalssotherpy indicated significant reductions in anxiety and depression scores. Specifically, repeated measures ANCOVA revealed a notable decrease in HAM-A (p = 0.012) and BDI (p < 0.001) scores, independent of age, gender, education, or diagnosis. These improvements suggest enhanced emotional regulation, increased self-esteem, and greater social participation.DiscussionThe findings align with previous research on water-based therapies, highlighting thalassotherapy’s holistic benefits. Importantly, the study demonstrates the potential to reduce pharmaceutical dependence, thereby lowering healthcare costs and minimizing medication side effects. Despite its promising outcomes, the research acknowledges limitations, including a relatively small sample size and lack of long-term follow-up. Future studies with larger, diverse populations and controlled comparisons are necessary to validate the sustainability and broader applicability of these findings. Overall, thalassotherapy emerges as a cost-effective, non-pharmacological intervention that can complement traditional treatments, offering a valuable approach to enhancing the physical and psychological health of individuals with disabilities.